Sustainable Production of Bulk Chemicals c - Xian, Mo.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
The book describes in detail the authors$1 (Bcurrent understanding of the models that incorporate the concepts and techniques of synthetic chemistry, chemical engineering, synthetic biology and bioengineering. These include chemical engineering methods for green chemical production from sustainable bio-resources; using synthetic chemistry and kinetics of chemical reaction concepts in the construction of non-natural enzymes and bio-pathways, partial integration of bioconversion steps in chemical synthesis routes; integration of chemo-, bio- conversion steps in one system; microbial production of chemicals from economic chemo-resourced chemicals; and chemical production of value-added derivatives from bio-based amino acids. It provides a valuable reference source for laboratory and industrial professionals in a number of chemical and biological disciplines such as synthetic chemistry, synthetic biology, chemical engineering, biotechnology, microbiology, molecular biology, etc. Dr. Mo Xian is a Professor at Qingdao Institute of Bioenergy and Bioprocess Technology, Chinese Academy of Sciences, Qingdao, China.s
Bulk chemical production: chemo-, bio- and integrated strategies -- Chemical conversion of biomass to green chemicals -- Design and construction of non-natural enzymes and bio-pathways to get more chemicals sustainably produced -- Incorporate bioconversion step in the chemical synthetic routes -- One-pot chemo-, bio- conversions for desired chemicals -- Microbial production of chemicals from economic bulk chemicals -- Chemical production of value added derivatives from bio-based amino acids.
Keywords: Life sciences; Renewable energy resources; Biotechnology; Biochemistry; Renewable energy sources; Alternate energy sources; Green energy industries; Life Sciences; Biochemistry, general; Renewable and Green Energy; Biotechnology; Electronic books